Alcohols, esters and heavy sulphur compounds production by pure and mixed cultures of apiculate wine yeasts - Moreira, Nathalie (2005)
Strains of Hanseniaspora uvarum, Hanseniaspora guilliermondii and Saccharomyces cerevisiae were used as pure or mixed starter cultures in commercial medium, in order to compare their kinetic parameters and fermentation patterns. In pure and mixed cultures, yeasts presented similar ethanol yield and productivity. Pure cultures of H. uvarum and S. cerevisiae showed a specific growth rate of 0.38 h⁻¹; however, this value decreased when these yeasts were grown in mixed cultures with H. guilliermondii. The specific growth rate of pure cultures of H. guilliermondii was 0.41 h⁻⁻¹ and was not affected by growth of other yeasts. H. guilliermondii was found to be the best producer of 2-phenylethyl acetate and 2-phenylethanol in both pure and mixed cultures. In pure cultures, H. uvarum led to the highest contents of heavy sulphur compounds, but H. guilliermondii and S. cerevisiae produced similar levels of methionol and 2-methyltetrahydrothiophen-3-one. Growth of apiculate yeasts in mixed cultures with S. cerevisiae led to amounts of 3-methylthiopropionic acid, acetic acid-3-(methylthio)propyl ester and 2- methyltetrahydrothiophen-3-one similar to those obtained in a pure culture of S. cerevisiae; however, growth of apiculate yeasts increased methionol contents of fermented media.